Kesejahteraan Ekonomi sebagai Upaya Pemeliharaan Perdamaian dan Pencegahan Konflik Baru di Aceh (Kajian pada Bantuan Keuangan Peumakmu Gampong) - Suadi - (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2011)
This paper aims to address Financial Aids for Village Prosperity (BKPG) was engaged by Aceh Government. How this program implicates to peacebuilding, peacekeeping, and new conflictpreventing post vertical conflict ”Aceh–Jakarata”. The financial aids were used more physical development (public infrastructure and health faciality) such as roads, irrigation, sanitation and village poly clinic (Polindes). The impact of BKPG to community welfare is difficult to measure accurately, but generally it has given many benefits to society, such as access to new jobs vacancy, have physical development that cause them easy and cheap to do economic activities. The development activities of BKPG has increased earnings, prosperity and welfare of the village community in Muara Batu eventhougt not maxmimum. Based on this realty, BKPG can be perceived has contributed to peacekeeping and conflict preventing, because peace made community better in economic and politic. Beside that no internal conflict was found while project conducted.Keywords: Ecomomic, Welfare, Peacekeeping and Conflictpreventing